MEDICINE OF ANCIENT GREECE - Dilnavoz Nishonova (Journal Park Publishing, 2023)
Science and culture are highly developed on the European continent countries were ancient Greece and Rome. That's all there is to it to other European countries from a political, social and cultural point of view relatively advanced. In the field of spiritual life and science great discoveries were made. Dozens of great scientists in these countries, philosophers, representatives of art and literature grew up. That's it there were also famous judges.
Keywords: mythology, human, anatomy, physiology, phytotherapy, health, illness, blood.